Effects of multiple stress events at different stages of life on the incidence of metabolic syndrome - Li, Na; Gao, Yuanyuan; Zhao, Xiaochuan; Wang, Lan; Wang, Ran; Song, Mei; Hu, Peihua; Lu, Wenting; Zhao, Tianyu; Huang, Fanfan; Liu, Bufan; Ren, Ruojia; et al. (Frontiers in Endocrinology, 2024)
Objective: To investigate the effects of multiple stress events in different stages of life on the incidence of metabolic syndrome (MetS). Methods: Miners from Tangshan, China, were recruited for this study. Workers of the Kailuan Mining Group were evaluated to investigate whether exposure to Tangshan earthquakes during the fetal period in 1976. Adult life events and childhood trauma were assessed separately via the Life Event Scale and Childhood Trauma Questionnaire. The subjects were physically examined and general demographic data such as waist circumference were collected. Blood samples were collected for measurement of metabolic parameters. Corticotropin releasing hormone(CRH) levels was measured by enzyme-linked immunosorbent assay (ELISA). The subjects were divided into four groups according to their exposure to traumatic events in different stages of life: no exposure group, 1-exposure group, 2-exposures group, and 3-exposures group. The incidence of MetS, metabolic parameters and CRH levels in each of the four groups was compared. Results: In all, 626 people were enrolled; of these, 183, 262, 150, and 31 were in the no exposure, 1-exposure, 2exposures, and 3-exposures groups, respectively. A remarkable variation in the incidence of MetS was observed among the four groups (x 2 =16.462, P<0.001). MetS incidence increased with the increasing number of traumatic events, except for in the no exposure group (17.9% in 1-exposure group, 24.7% in 2-exposure group, and 48.4% in the 3-exposure group). Multivariate logistic regression analysis showed that exposure to multiple stress during the fetal, childhood, and adult stages of life represent independent risk factors for developing MetS (OR=3.134, 95%CI=1.042-9.429). Smoking increased the risk of developing MetS (OR=1.809, 95%CI=1.140-2.871). Conclusions: Exposure to multiple traumatic events in distinct life stages increases the risk of developing MetS. Smoking is a risk factor for developing MetS.